ASSESSMENT OF FOOD SECURITY AND DIETARY DIVERSITY OF FONIO (Digitaria spp.) FARMING HOUSEHOLDS IN PLATEAU STATE, NIGERIA - Folorunso, Solomon; Makwin, F. M. (FUDMA JOURNAL OF SCIENCES, 2022)
The study assessed the food security and dietary diversity among Fonio farming households in Jos-South LGA, Plateau state, Nigeria. A multi-stage sampling technique was used to select 157respondents for the study. Primary data was used for this study through the administration of a well-structured questionnaire aided by interview schedule. The analytical techniques used include descriptive statistics, USDA Food Security model, Dietary Diversity score and Logit Regression model. The results of the socioeconomic characteristics; age, marital status, household size, education, farming experience, farm size, membership of cooperative societies, access to credit and access to extension services were identified and described. The result of household food dietary diversity indicates that 64% of the respondents’ households had high food dietary diversity while 36% accounted for low household food dietary diversity. The result further indicates that 14% of the households consumed cereals, followed by legumes (14.49%), milk had 1.75%, and eggs had 2.47%. Oil/fats, Meats, Vegetables and Roots and Tubers accounted for 13.13%, 9.99%, 7.66% and 6.59% of the respondents’ households respectively. The result of logit regression indicated that the coefficients of age, household size, farm size, cooperative membership, and access to credit were significant. The study recommend that government should make credit accessible through the anchor borrower’s scheme, inputs heavily subsidized easily through the anchor borrower’s scheme and there should be education of farming households on different classes of food for healthy living through the National Orientation Agency